Heavy Metals in Soils and the Remediation Potential of Bacteria Associated With the Plant Microbiome - González Henao, Sarah; Ghneim-Herrera, Thaura (Frontiers in Environmental Science, 2021)
High concentrations of non-essential heavy metals/metalloids in soils and irrigation water represent a threat to the environment, food safety, and human and animal health. Microbial bioremediation has emerged as a promising strategy to reduce the concentration of heavy metals in the environment due to the demonstrated ability of microorganisms to sequester and transform these compounds. Although several bacterial strains have been reported as capable of remediation of heavy metals, published information has not been comprehensively analyzed to recommend the most efficient microbial resources for application in bioremediation or bacterial-assisted phytoremediation strategies. In this study, we critically analyzed eighty-five research articles published over the past fifteen years, focusing on bacteria-assisted remediation strategies for the heavy metals, arsenic, cadmium, and lead, and selected based on four criteria: i) The bacterial species studied are part of a plant microbiome, i.e. they interact closely with a plant species ii) these same bacterial species exhibit plant growth-promoting characteristics, iii) bacterial resistance to the metal(s) is expressed in terms of the Minimum Inhibitory Concentration (MIC), and iv) metal resistance is related to biochemical or molecular mechanisms. A total of sixty-two bacterial genera, comprising 424 bacterial species/strains associated with fifty plant species were included in our analysis. Our results showed a close relationship between the tolerance level exhibited by the bacteria and metal identity, with lower MIC values found for cadmium and lead, while resistance to arsenic was widespread and significantly higher. In-depth analysis of the most commonly evaluated genera, Agrobacterium, Bacillus, Klebsiella, Enterobacter, Microbacterium, Pseudomonas, Rhodococcus, and Mesorhizobium showed significantly different tolerance levels among them and highlighted the deployment of different biochemical and molecular mechanisms associated with plant growth promotion or with the presence of resistance genes located in the cad and ars operons. In particular, the genera Klebsiella and Enterobacter exhibited the highest levels of cadmium and lead tolerance, clearly supported by molecular and biochemical mechanisms; they were also able to mitigate plant growth inhibition under phytotoxic metal concentrations. These results position Klebsiella and Enterobacter as the best potential candidates for bioremediation and bacteria-assisted phytoremediation strategies in soils contaminated with arsenic, cadmium, and lead.